Climate vs. nutrient control: A global analysis of driving environmental factors of wetland plant biomass allocation strategy. (20th June 2023) - Pan, Yueyan; Zhang, Zhenming; Zhang, Mingxiang; Huang, Peisheng; Dai, Liyi; Ma, Ziwen; Liu, Jiakai
Abstract: Wetland plant biomass and its allocation are sensitive to environmental changes, and they make up a significant part of the carbon pool in wetlands. Here, we collected global data on wetland plant biomass from 1980 to 2021. Based on an analysis of 1134 observations from 182 published papers on wetland ecosystems, we generated spatially explicit global maps of belowground biomass (BGB) to aboveground biomass (AGB) ratio of wetland plants. Our study found that AGB is higher in tropical mangrove regions while BGB is higher in cold regions at high latitudes. AGB did not show a significant response to any individual environmental factors ( p  > 0.05). In the contrast, plant BGB is influenced by total phosphorus ( p  < 0.05) but not total nitrogen, and extreme temperatures are the main driver of plant BGB ( p  < 0.05). Compared to climate factors, soil nutrients were the main factor affecting plant biomass allocation in different wetland types. The relationships between the wetland plant biomass and their environmental conditions are discussed, which provided a basis for further understanding the conservation of wetland plants under environmental change. Graphical abstract: Image 1